"Here we give advice for free": the functioning of plant clinics in Rwanda. Issue 7 (3rd October 2018) - Majuga, Jean Claude N.; Uzayisenga, Bellancile; Kalisa, Jean Pierre; Almekinders, Conny; Danielsen, Solveig
ABSTRACT: Although plant clinics are considered an important mechanism in the service delivery to farmers, not much is known about their functioning in the daily reality of plant doctors and farmer-clients. This article reports on an exploratory study describing the functioning of eight plant clinics in Rwanda. Personal and organisational commitment, publicity, and proactive communication with farmers and local leaders are key factors explaining higher attendance of some clinics. Farmer attendance is under-reported by 40–50%. Data management needs improvement to make clinic records reliable tools for decision-makers. This type of assessment can help improve operations and realise the plant clinics' potential.